Trends in fish community structure and recruitment in a temporarily open/closed South African estuary - James, Nicola Caroline (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2007)
Long-term interannual changes in richness, abundance, diversity and structure of the fish community in the temporarily open/closed East Kleinemonde Estuary, Eastern Cape, are described and the recruitment success of two estuary-dependent marine species assessed. In addition, laboratory experiments were conducted to assess the possible role of olfaction in the recruitment process of an estuary-dependent marine fish species. Multivariate analyses of the annual marine fish communites identified two distinct groups with more species recorded during years that succeeded spring (September to November) mouth opening events than in years following no mouth opening events in spring. Interannual community stability (IMD) and seriation (IMS) also increased from the 'other' to the 'spring' years. These results highlight the importance of the timing of mouth opening to the marine fish community in a temporarily open/closed estuary. This study also made use of long-term records of daily mouth state and linked them to the recruitment of distinct year-class cohorts in two spardis with contrasting lifehistory characteristics. Lithognathus lithognathus only recruited into the estuary in years when the mouth opened between late August and January. This was linked to the limited spawning season of this species and its inability to enter closed estuaries via wave overwash events. In contrast, recruitment by Rhabdosargus holubi juveniles appeared to be uninterrupted and was not determined by the seasonality of mouth opening. This species dominates the marine-spawning component of the East Kleinemonde Estuary and its success is attributed to an extended spawning season and its ability to recruit into estuaries during both overwash and open mouth conditions. Attraction of postflexion Rhabdosargus holubi larvae to estuary, surf zone and river water was also measured using a rectangular choice chamber. In two sets of experiments, conducted during peak recruitment periods, larvae from both the surf zone and estuary mouth region selected estuary water with a significantly higher frequency than sea water. Larvae collected in the mouth region showed a stronger preference for river water than those collected in the surf zone, thus suggesting that these fish are more attracted to freshwater influenced nursery areas once they have entered the estuary than those in the surf zone. Larvae collected in the marine environment also selected surf zone water with significantly higher frequencies than estuary water or offshore sea water, thus confirming the importance of the surf zone as an interim nursery area for postflexion R. holubi.
Keywords: Fish communities -- South Africa -- Eastern Cape; Marine fishes -- South Africa -- Eastern Cape; Estuarine fishes -- South Africa -- Eastern Cape; Estuarine ecology -- South Africa -- Eastern Cape